DEVELOPMENT OF CHEMISTRY LEARNING OUTCOME ASSESSMENT INSTRUMENTS (MULTIPLE CHOICE) ON HYDROCARBON MATERIAL - Manullang, Enjelika; Daulay, Rabiah Afifah; Nadira, Fathin; Sihaloho, Kayra Aprilia Yosephin; Azhara, Nazwa; Nazihah, Nazwa (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to develop an assessment instrument in the form of a multiple-choice objective test on hydrocarbon material in senior high school chemistry. The research method used is research and development (RD), involving steps such as material analysis, test item construction, validation, field trials, and item analysis. The developed instrument consists of 30 items based on the learning outcomes in the